The influence of the hand`s acceleration and the relative contribution of drag and lift forces in front crawl swimming - Gourgoulis, V.; Boli, A.; Aggeloussis, N.; Antoniou, P.; Toubekis, A.; Mavromatis, G. (Journal of Sports Sciences, 2015)
The aim of this study was to assess the effect of the hand`s acceleration on the propulsive forces and the relative contribution of the drag and lift on their resultant force in the separate phases of the front crawl underwater arm stroke. Ten female swimmers swam one trial of all-out 25-m front crawl. The underwater motion of each swimmer`s right hand was recorded using four camcorders and four periscope systems. Anatomical landmarks were digitised, and the propulsive forces generated by the swimmer`s hand were estimated from the kinematic data in conjunction with hydrodynamic coefficients. When the hand`s acceleration was taken into account, the magnitude of the propulsive forces was greater, with the exception of the mean drag force during the final part of the underwater arm stroke. The mean drag force was greater than the mean lift force in the middle part, while the mean lift force was greater than the mean drag force in the final part of the underwater arm stroke. Thus, swimmers should accelerate their hands from the beginning of their backward motion, press the water with large pitch angles during the middle part and sweep with small pitch angles during the final part of their underwater arm stroke.